2013
DOI: 10.1007/s00264-013-2002-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of Morton's neuroma: clinical results after open excision

Abstract: Purpose Long-term results following surgical treatment of Morton neuroma are rare. The purpose of the present study was to evaluate patients after excision of Morton's neuroma at least ten years following surgery. Methods We performed a retrospective review of the patients' records who underwent excision of an interdigital neuroma with the clinical diagnosis of Morton's neuroma. Eighty-one patients who had undergone surgery on 98 feet were analysed at an average of 15.3 years postoperatively. In total 111 neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 28 publications
5
55
0
2
Order By: Relevance
“…Although this is a relatively common problem, the general belief is that it does not influence patient satisfaction (3,6). In our study as well, 35% of the patients reported that they rarely felt mild pain in the surgery area.…”
Section: Characteristic Valuesupporting
confidence: 55%
See 1 more Smart Citation
“…Although this is a relatively common problem, the general belief is that it does not influence patient satisfaction (3,6). In our study as well, 35% of the patients reported that they rarely felt mild pain in the surgery area.…”
Section: Characteristic Valuesupporting
confidence: 55%
“…Neuroma and the excision process of the branches (neurectomy) that are performed through dorsal or plantar approaches are the most effective treatment methods (3).…”
Section: Introductionmentioning
confidence: 99%
“…). Pre‐operative evaluation of the forefoot is thus important: apart from allowing a search for fascial thinning, it can also rule out the bone deformities often associated with Civinini–Morton's syndrome (Kasparek & Schneider, ).…”
Section: Discussionmentioning
confidence: 99%
“…Kasparek et al 3 reported good clinical results, although sensory deficits were very common, fair results were found in 15% of patients and poor results in 8%. Complications after Morton surgery may require further regenerative surgical interventions.…”
Section: Discussionmentioning
confidence: 97%